Hydraulic Optimization of Inflow System of Bidirectional Drainage Pumping Station in Pump-sluice Complex Engineering - XIAO Zhiqiao; FEI Zhaodan; QIAN Shangtuo (Renmin Zhujiang)
To improve the adverse flow pattern such as circling and recirculation in the lateral forebay of the lateral inflow pumping station, numerous simulations of the flow during the operation of the pumping station in the pump-sluice complex engineering were conducted based on the RNG k-ε model, and the rectification measures for the lateral forebay of the lateral contraction inflow pumping station were proposed. The numerical results indicate that: the circling flow occurred in the forebay due to the effect of lateral contraction, resulting in recirculation flow forming in the suction sump due to the combination of circling flow and downward swirling flow. This leads to a lower axial-flow uniformity in the flow channels of the pumping station, indicating a poor inflow condition. Diversion piers in the inflow contraction area can effectively improve the flow pattern, inhibit the formation of recirculation flow, and increase the uniformity of inflow. The length of the diversion pier was optimized and the rectification of the optimized scheme was verified by the hydraulic model test. The research results can provide technical references for the flow analysis and optimization of the lateral inflow system of the pumping station in the pump-sluice complex engineering.